2020
DOI: 10.1002/jgc4.1266
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives from individuals with familial hypercholesterolemia on direct contact in cascade screening

Abstract: Familial hypercholesterolemia (FH) is the most common genetic cardiovascular disorder and is characterized by severely elevated low-density lipoprotein cholesterol (LDL-C) at a young age. Men with FH have a greater than 50% risk for coronary heart disease (CHD) by 50 years of age, and women have a greater than 30% risk for CHD by 60 years of age (Ito, McGowan, & Moriarty, 2011). The estimated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…The implications of a genetic literacy program to address these barriers found that providers improved their understanding about genetics and ability to provide accurate knowledge and advice while promoting genetic literacy to patients [13]. Similarly, for cascade screening of relatives, an international survey explored perspectives of patients on indirect and direct contact approaches for cascade screening and found that a majority of individuals supported direct outreach by their provider to their relatives to share their FH result [14]; however, this approach is seldom used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The implications of a genetic literacy program to address these barriers found that providers improved their understanding about genetics and ability to provide accurate knowledge and advice while promoting genetic literacy to patients [13]. Similarly, for cascade screening of relatives, an international survey explored perspectives of patients on indirect and direct contact approaches for cascade screening and found that a majority of individuals supported direct outreach by their provider to their relatives to share their FH result [14]; however, this approach is seldom used.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 153 articles in the improving care category, 116 were excluded, as they were relevant but either did not map to implementation strategies, focused on pediatric care, published between 2018 and 2020, duplicates, or not available in English. The remaining 37 were categorized into the following implementation strategies: 'assess for readiness and identify barriers and facilitators' [9], 'develop and organize quality monitoring systems' [14], 'create new clinical teams' [2], 'facilitate relay of clinical data to providers' [4], and 'involve patients and family members' [8]. Table 2 lists and defines the mapped ERIC implementation strategies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a rule, our interviewees acknowledged the importance and urgency of sharing health-related genetic information among relatives who might benefit from such knowledge. However, they also identified several emotional and logistic challenges, such as geographical distances, lack of social contact and tense relations which have previously been described in patients and genetic counselees [31,36,43,47,48]. One way to understand the swell of negative emotions in these situations is that they are caused by conflicting duties.…”
Section: A Complex Topic Eliciting Worry and Concern For Othersmentioning
confidence: 97%
“…There are a variety of reasons for underdiagnosis of FH, including lack of systematic cholesterol screening in children and adults and a lack of awareness about FH among healthcare clinicians [ 5 , 6 , 7 , 8 ]. Two distinct and complementary initiatives in the U.S. to improve identification of FH include automated screening approaches of health-related data to identify those with possible FH and enhanced family communication methods and tools to improve cascade testing uptake by at-risk relatives [ 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%